2014
DOI: 10.1080/09589236.2013.877383
|View full text |Cite
|
Sign up to set email alerts
|

Sixth form girls and bisexual burden

Abstract: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…What I say about for myself depends on the situation because I may or may not be attracted to that man or woman." He explained that this was partly due to bisexual burden ( Anderson et al, 2014), an umbrella term to understand the range of stereotypes and prejudices bisexuals traditionally encounter:…”
Section: Generational Differences In Identifying As Bisexualmentioning
confidence: 99%
See 1 more Smart Citation
“…What I say about for myself depends on the situation because I may or may not be attracted to that man or woman." He explained that this was partly due to bisexual burden ( Anderson et al, 2014), an umbrella term to understand the range of stereotypes and prejudices bisexuals traditionally encounter:…”
Section: Generational Differences In Identifying As Bisexualmentioning
confidence: 99%
“…This fear seems to have been unfounded, however, given the complexity of life experience that is recognized in the literature that charts the progressive changes for sexual minority youth (e.g. Anderson, McCormack & Ripley, 2014;McCormack, 2012b;Morris, 2014), as well as research that focuses on negative experiences (e.g. Robinson & Espelage, 2011).…”
mentioning
confidence: 99%
“…Scholarship on sexualities has mapped the changing experiences of lesbian, gay and bisexual (LGB) youth over the past two decades (Morris et al ., ; Anderson et al ., ,b). For example, while educational research in the 1980s and 1990s found high levels of homophobia in the UK (Mac an Ghaill, ; Epstein & Johnson, ; Thurlow, ), the experiences of gay and lesbian students in the twenty‐first century have seen a significant improvement (McCormack, ,b, ; Blanchard et al ., ; White & Hobson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, opposite to the newer literature on western masculinities (Anderson, McCormack, & Ripley, 2016;Branfman, Stiritz, & Anderson, 2016;Kian, Anderson, Vincent, & Murray, in press;Morris & Anderson, online first;Scoats, Joseph, & Anderson, in press) some of the 1980s and 1990s western literature on men, sport and sexuality, situated within an Anglo-American culture of homohysteria, somewhat applies within the Tunisian context. As cultural awareness that homosexuality exists grows, this will, likely, increasingly apply.…”
Section: Discussionmentioning
confidence: 84%